2021
DOI: 10.3389/fncel.2021.773375
|View full text |Cite
|
Sign up to set email alerts
|

Neural Stem Cells Overexpressing Nerve Growth Factor Improve Functional Recovery in Rats Following Spinal Cord Injury via Modulating Microenvironment and Enhancing Endogenous Neurogenesis

Abstract: Spinal cord injury (SCI) is a devastating event characterized by severe motor, sensory, and autonomic dysfunction. Currently, there is no effective treatment. Previous studies showed neural growth factor (NGF) administration was a potential treatment for SCI. However, its targeted delivery is still challenging. In this study, neural stem cells (NSCs) were genetically modified to overexpress NGF, and we evaluated its therapeutic value following SCI. Four weeks after transplantation, we observed that NGF-NSCs si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Furthermore, VitD can enhance neural stem cell proliferation and differentiation into neurons and oligodendrocytes ( 85 , 86 ). It would be interesting to explore whether VitD could interact with neural stem cells to promote neurons and myelin regeneration after SCI via enhancing and modulating endogenous neurogenesis ( 87 89 ). Recent literature indicated that small molecules combined with collagen hydrogel directed neurogenesis and migration of neural stem cells after implantation in the lesioned spinal cord ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, VitD can enhance neural stem cell proliferation and differentiation into neurons and oligodendrocytes ( 85 , 86 ). It would be interesting to explore whether VitD could interact with neural stem cells to promote neurons and myelin regeneration after SCI via enhancing and modulating endogenous neurogenesis ( 87 89 ). Recent literature indicated that small molecules combined with collagen hydrogel directed neurogenesis and migration of neural stem cells after implantation in the lesioned spinal cord ( 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the presence of either EGF/bFGF or NGF is essential for NPSC EV bioactivity, with NGF alone producing more consistently enhanced PC-12 neurite outgrowth compared to EGF/bFGF alone. Recently, engineering NPSCs to overexpress NGF was shown to enhance SCI recovery in mice following transplantation of these cells into the lesion area 49 . A well-recognized advantage of EVs is their ability to transport and deliver bioactive cargo.…”
Section: Discussionmentioning
confidence: 99%
“…These “primed” NSCs showed decreased Notch and BMP signaling and an increase in lineage-specific transcription factors and protein synthesis (i.e., EGFR, cyclin-dependent kinase 2 (CDK2)) [ 80 ]. With regard to neural repair, modulating the activation state of forebrain NSCs by pulling them out of quiescence has been shown to result from injury alone, as well as following the administration of growth factors, cytokines and drugs [ 61 , 92 , 93 , 94 , 95 , 96 ] Indeed, brain repair and improved functional outcomes have been correlated with the activation of endogenous NSCs [ 91 , 97 , 98 , 99 ].…”
Section: Adult Neural Stem Cells: a Heterogeneous Population Of Cellsmentioning
confidence: 99%